Newspaper cuttings - Buckman, John Sydney Vernon (1919)
Volumes numbered 1-5 comprise a selection of clippings from Australian newspapers 1929-1935 on aspects of Australian history. Vol. 5 is devoted to the centenary of Victoria 1835-1935; the folio volume (unnumbered) contains historical articles on Sydney. These clipings are not identified as to the title or date of the newspapers but appear to be about 1919.
Manuscript reference no. : NLA MS 6289.
Keywords: Australia -- History; Victoria -- History; Sydney (N.S.W.) -- History